DETECÇÃO DE BACTÉRIAS LÁTICAS PRODUTORAS DE BACTERIOCINAS EM LEITE E QUEIJO - Schmidt, Jéssica T.; Funck, Graciele D.; Vicenzi, Raul; Richards, Neila; Hermanns, Gislaine (Salão do Conhecimento, 2013)
Resumo